Regulasi emosi pada pasien Covid-19 - Nabilah Dina Humaidah; Faulina Adma; Rozi Sastra Purna (Jurnal Psikologi Tabularasa, 2021)
This study aims to look at the regulation of emotions in Covid-19 patients. The qualitative approach used is descriptive method. Two early adults who contracted Covid-19 were recruited as study participants. Data was collected from interviews, observations, and relevant documents. Thompson's concept of the aspect of emotional regulation, namely emotions monitoring, emotions evaluating, emotions modification is used to provide psychological insights in analyzing data. This study found that the emotional regulation that occurs in Covid-19 patients fulfills every aspect, that participants are able to understand and realize everything that happens to them, are able to manage negative emotions, and be able to motivate themselves even with the help of family, friends or social media.